A method of real-time monitoring beam output stability of intense pulsed ion beam; Acta Physica Sinica; Vol. 72, iss. 17 - Xu Mo-Fei; Yu Xiang; Zhang Shi-Jian; Remnev (Remnyov) G. E. Gennady Efimovich; Le Xiao-Yun (2023, 2023)
Title screen